2001
DOI: 10.1038/sj.onc.1204350
|View full text |Cite
|
Sign up to set email alerts
|

Efficient rejoining of radiation-induced DNA double-strand breaks in vertebrate cells deficient in genes of the RAD52 epistasis group

Abstract: Rejoining of ionizing radiation (IR) induced DNA DSBs usually follows biphasic kinetics with a fast (t 50 : 5 ± 30 min) component attributed to DNA-PK-dependent non-homologous endjoining (NHEJ) and a slow (t 50 : 1 ± 20 h), as of yet uncharacterized, component. To examine whether homologous recombination (HR) contributes to DNA DSB rejoining, a systematic genetic study was undertaken using the hyper-recombinogenic DT40 chicken cell line and a series of mutants defective in HR. We show that DT40 cells rejoin IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 147 publications
(106 citation statements)
references
References 103 publications
7
99
0
Order By: Relevance
“…Therefore, no contribution of Rad51-dependent HR in the direct removal of radiation-induced Dsb as measured by the FAR assay is evident from these data. In this respect, Wang et al (2001) also have shown that HR did not measurably contribute to the removal of radiation-induced Dsb, even under conditions where NHEJ is compromised.…”
Section: -Test)mentioning
confidence: 81%
“…Therefore, no contribution of Rad51-dependent HR in the direct removal of radiation-induced Dsb as measured by the FAR assay is evident from these data. In this respect, Wang et al (2001) also have shown that HR did not measurably contribute to the removal of radiation-induced Dsb, even under conditions where NHEJ is compromised.…”
Section: -Test)mentioning
confidence: 81%
“…This would be consistent with our data evidencing an apparently normal early DNA repair-associated disappearance of g-H2AX foci, regardless of Chk2 expression, at least after low-dose IR. Given the delay with which Chk2 is activated (relative to rapid activation of ATM), we cannot exclude that DSBs resistant to a first wave of repair activity (Nunez et al, 1995;Wang et al, 2001) could function as an activating signal for Chk2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In DNA-PKcs de®cient cells, however, the contribution of the fast component is reduced without a measurable change in the half time, and the slow component, acting quasi as a backup, removes a substantially larger proportion of DNA DSBs (*70%). Interestingly, DNA DSB repair proceeds to similar ®nal levels in DNA-PKcs pro®cient and DNA-PKcs de®cient cells Nevaldine et al, 1997;Wang et al, 2000).…”
Section: Repair Inhibition In Caffeine Radiosensitizationmentioning
confidence: 99%